Characteristics of animal movement and environmental data for dynamic ocean management: Insights and guidance - Laura H. McDonnell; Elliott L. Hazen; Katharine J. Mach (Conservation Science and Practice)
Abstract Dynamic ocean management (DOM) is a critical approach for protecting highly migratory species amid environmental variability and change. We conducted an adapted systematic review to assess how animal movement and environmental data are used in DOM applications, identifying key data traits, barriers, and research priorities. Animal tag data inform initial assessments of species distributions, development of habitat models, near real‐time model inputs, and iterative model evaluation for dynamic management. In documented examples, effective translation of scientific insights into dynamic management products has resulted from early communication between researchers and stakeholders, integration of environmental and fisheries‐dependent data into advanced habitat modeling approaches, and reformatting of outputs for interdisciplinary needs. However, challenges persist around data gaps, science‐policy translation, and technical capacity limitations. Our findings highlight the importance of intentional, collaborative data collection, translation, and sharing to enable dynamic, climate‐resilient management of migratory species. We demonstrate DOM's adaptability and provide guidance for researchers and practitioners to contribute and use impactful data that informs responsive management decision‐making.